Reduced Growth and Nitrogen Uptake During Waterlogging at Tillering Permanently Affect Yield Components in Late Sown Oats - Arduini, Iduna; Baldanzi, Marco; Pampana, Silvia (Frontiers in Plant Science, 2019)
In Mediterranean Europe, winter cereals can experience soil waterlogging starting from crop establishment up to stem elongation and, in late sowings, this stress is combined with temperatures favorable to plant metabolism. Oats response to waterlogging has been rarely investigated, but these species seems to recover better than other cereals. In a two-year experiment, Avena sativa and A. byzantina were sown at the end of winter in pots placed outdoors. At the two-tiller stage, plants were exposed to waterlogging for periods ranging from 0 to 35 days. The dry weight and the N-concentration of shoots and roots were determined on waterlogged plants and drained controls at the start and the end of each waterlogging period, and at maturity. At maturity, the grain yield and its components were determined. To relate oat response to its specific morphological and developmental traits, results were compared to the published results in wheat and barley. Both oat species suffered severe damage during waterlogging: the uptake of nitrogen and the N-concentration of shoots were reduced after 7 days; tiller initiation and root growth after 14 days and shoot growth after 21 days. All plants survived waterlogging, and the relative growth rates of roots and shoots, and the net uptake rate of nitrogen were resumed during recovery. Nevertheless, at maturity, the straw and root biomass were markedly lower with all waterlogging durations, and grain yield decreased by 42% up to approximately 81% following an asymptotic equation. The most affected yield components were the number of panicles per plant and the number of kernels per panicle, but their relative sensitivity changed according to waterlogging duration. The slight increase in tiller fertility in response to short waterlogging and the small and irregular decrease in the number of kernels per spikelet suggest that the two oats could recover the initiation and size of inflorescences better than other winter cereals. Despite this, waterlogging in spring was highly detrimental to these oats because of severe damage under waterlogging and because of the inability to initiate new tillers and adequately resume root growth during recovery, once plants had achieved the phase of stem elongation.